Discordance in Couples Pregnancy Intentions and Breastfeeding Duration: Results from the National Survey of Family Growth 2011–2013 - Jordyn T. Wallenborn; Gregory Chambers; Elizabeth P. Lowery; Saba W. Masho (Journal of Pregnancy)
Background. Parental disagreement in pregnancy intention elevates the risk of adverse health events for mother and child. However, research surrounding parental pregnancy intention discrepancies and breastfeeding duration is limited. This study aims to examine the relationship between couple’s discordant pregnancy intention and breastfeeding duration. Methods. Data from the 2011–2013 National Survey of Family Growth was analyzed. Parental pregnancy intention was categorized as “intended by both parents,” “unintended by both parents,” “father intended and mother unintended,” and “father unintended and mother intended.” Breastfeeding duration was categorized as “never breastfed,” “breastfed less than six months,” and “breastfed at least six months.” Multinomial logistic regression, odds ratios, and 95% confidence intervals were calculated. Results. Couples with a concordant unintended pregnancy were more likely to have a child who was never breastfed or breastfed less than six months compared to couples with a concordant intended pregnancy. Similarly, couples with a discordant pregnancy were more likely to have a child who was never breastfed or breastfed less than six months. Conclusions. Findings from this study show a relationship between couples’ pregnancy intentions and subsequent breastfeeding behaviors. Healthcare professionals should be cognizant of parents’ differing opinions surrounding pregnancy intention and the implications on breastfeeding outcomes.